Comparison of the environmental impact of the CRIMSON process with normal sand casting process - Zeng, Binxu; Salonitis, Konstantinos; Jolly, Mark R. (Cranfield University, 2013)
The CRIMSON process is an alternative process to conventional casting that can be used for small to medium batch sizes. The aim of this process are to improve the casting quality and reduce the energy consumption within light-metal casting industry. Nowadays, the energy efficiency becomes more and more important. This is not only about the cost of the production, but also about the environmental effect. In this paper, the CRIMSON process will be compared with the conventional sand casting process. The Life cycle assessment (LCA) method will be used to assess the environmental impact of both casting processes.
Keywords: CRIMSON, casting, energy saving, Life Cycle Assessment